Exercise During Pregnancy Protects Against Hypertension and Macrosomia: Randomized Clinical Trial. Issue 9 (September 2016) - Barakat, Ruben; Pelaez, Mireia; Cordero, Yaiza; Perales, Maria; Lopez, Carmina; Coteron, Javier; Mottola, Michelle F.
Abstract : (Abstracted from Am J Obstet Gynecol 2016;214:649.e1–649.e8) Up to 10% of all pregnancies are affected by some form of hypertension, with the rates of diagnosis varying according to the country, population studied, and the criteria used to diagnose the problem. Since these clinical issues may range in severity, elevated blood pressure remains a leading cause of maternal, fetal, and neonatal morbidity and mortality.